Alkali-activated binders – A sustainable alternative to OPC for stabilization and solidification of fly ash from municipal solid waste incineration. (20th December 2022) - Labianca, Claudia; Ferrara, Carmen; Zhang, Yuying; Zhu, Xiaohong; De Feo, Giovanni; Hsu, Shu-Chien; You, Siming; Huang, Longbin; Tsang, Daniel C.W.
Abstract: This research aims to evaluate the sustainability of alkali-activated binders for the stabilization/solidification (S/S) of municipal solid waste incineration fly ash (MSWI FA). A detailed environmental assessment of different alkali-activated mixtures was conducted using life cycle assessment (LCA) to identify the factors affecting their environmental burden. Ground granulated blast-furnace slag (GGBS) and metakaolin (MK) were used as the precursors. Results showed that all the alkali-activated blocks fulfilled the requirements for landfill and reuse as fill materials. Adopting alkali activation for S/S of MSWI FA instead of OPC allowed up to 70% reduction of global warming potential. However, in other impact categories such as human toxicity and land use, the alkali mixtures recorded higher values than the mix with OPC (+60–70%), primarily because of the impacts related to the production of chemical activators. The sensitivity analysis demonstrated that alternative production methods for sodium silicate and sodium hydroxide could enormously reduce the impacts related to the alkali solution. When the hydrothermal method for sodium silicate and the ODC method for sodium hydroxide were adopted, a reduction of 71%, 22%, and 24% was recorded in global warming potential, fossil resource scarcity, and human toxicity categories, respectively, compared with the mix with OPC. Therefore, this study sheds light on alkali-activated materials as sustainable S/S alternative to OPC for hazardous waste management to promote carbon neutrality. Graphical abstract: Image 1 Highlights: Alkali-activated S/S can allow the CO2 eq emission reduction between 55 and 71%. Alternative alkali production routes reduced impacts in HT and FRS by 23 and 28%. The ODC method revealed great potential for sodium hydroxide production. The hydrothermal route was more sustainable than the furnace for sodium silicate. The binary system with GGBS:MK ratio of 7:3 showed the best mechanical performance.